Influence of socioeconomic factors on COVID-19 mortality in children: a scoping review - Bianca Chel da Silva; Ana Cristina Ribeiro; Silvia Carla da Silva André Uehara (Rev Rene)
Objective: to identify the scientific evidence on the relationship between socioeconomic factors and mortality in children due to COVID-19. Methods: this is a scoping review. Searches were carried out in the following databases: US National Library of Medicine - National Institutes of Health; Scientific Electronic Library Online; Institute for Scientific Information; Cumulative Index to Nursing and Allied Health Literature; and SciVerse Scopus. Results: 15 articles were selected that showed the influence of socioeconomic factors on infant mortality from Severe Acute Respiratory Syndrome Coronavirus 2. Conclusion: it was shown that socioeconomic factors are related to increased mortality from COVID-19 in the infant population, low income and residence in locations considered to be of greater socioeconomic vulnerability, which were presented as important variables to be considered in the COVID-19 pandemic. Contributions to practice: several factors are related to increased susceptibility to Severe Acute Respiratory Syndrome Coronavirus infection and worsening of the disease in children. However, understanding that socioeconomic factors can be a determinant of COVID-19 incidence and mortality in children highlights the need to invest in actions aimed at reducing socioeconomic inequalities, to reduce preventable deaths.